Overcoming recruiting and retain challenges of operational workers - Mendes, P.; Pereira, L.; Lopes da Costa, R.; Dias, Á.; Gonçalves, R. (International Journal of Work Organisation and Emotion, 2023)
There is a chronicle shortage in skilled and non-skilled workers for the construction and engineering services industries. This issue leads to a major challenge for companies operating in these sector – how to overcome the challenges to recruit and retain operational workers for these industries. The main goal for this assignment was to identify strategies and solutions that might help companies to overcome this concern. In that regard, the ‘Pereira problem solving research methodology’ was employed, to better understand the underlying causes, trend and main impacts of this matter, while also being able to uncover possible solutions and its expected benefits. The results show that companies need to address both ends of the issue – recruitment and retention – in a proactive and effective manner, to be able to ensure its operational teams’ growth and stability, thus guaranteeing its business sustainability.